Repairing corporate legitimacy after crisis : a study on Volkswagen’s effort to win back trust after emissions scandal - Kähkönen, Aku (My University, 2019)
The multinational car manufacturer Volkswagen AG was in September 2015 found to have used illegal defeat devices in its diesel vehicles to cheat emissions testing. With the help of the defeat device Volkswagen was able to artificially lower its cars’ emissions during emissions testing and therefore sell them on markets with strict emissions regulation. A thorough investigation unveiled that the firm’s deception had endured for more than a decade and put the firm in the midst of a major crisis, which threatened the company’s legitimacy. Volkswagen reacted to the crisis with an intensive legitimacy management strategy and was able to regain its position as the largest car manufacturer in the world just a few years after the scandal. How is this possible and which legitimacy repairing actions did Volkswagen use in its successful legitimacy management strategy after the crisis? Although Volkswagen is still recovering from the crisis, its initial legitimacy repairing actions and communication can be discovered from the 25 press releases of the firm after the outburst of the crisis. The press releases are analysed with the help of Suchman’s legitimacy management framework, which is based on legitimacy theory. Systematic content analysis is used as the method in this qualitative research. The framework makes it possible to discover legitimacy repairing actions in Volkswagen's communication and extract content and meanings from them. The main findings of this study are that Volkswagen used a wide variety of different actions to repair its legitimacy. The combination of actions was also more important than individual actions alone. Some of the actions were targeted at individual stakeholder groups and Volkswagen’s use of actions developed over time. A concluding discovery of Volkswagen’s legitimacy management is that the legitimacy repairing actions were used in collaboration to build a compelling story of Volkswagen’s transition to sustainable electric mobility in the future. The aim of the transition was to change the way the company would be interpreted in future by its stakeholders, and thus ultimately repair the company’s legitimacy. Finally, this study provides possible future research avenues for legitimacy management of major crisis.
Keywords: Volkswagen, emissions scandal, legitimacy theory, corporate legitimacy management, crisis management, press releases, content analysis